2007
DOI: 10.1016/j.vetmic.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid testing leads to the underestimation of the scrapie prevalence in an affected sheep and goat flock

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.A c c e p t e d M a n u s c r i p t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(43 reference statements)
2
13
0
Order By: Relevance
“…Previous work had suggested that examination of LRS tissues in addition to brain provides better estimates of scrapie infection in sheep [13,25,28]. Our results are a noticeable example that this is also the case in goats and that, in agreement with those earlier sheep studies, the medial retropharyngeal lymph node would be the sample of choice, together with the obex, for post-mortem surveillance.…”
Section: Implications For Surveillance Of Goat Tsesupporting
confidence: 88%
“…Previous work had suggested that examination of LRS tissues in addition to brain provides better estimates of scrapie infection in sheep [13,25,28]. Our results are a noticeable example that this is also the case in goats and that, in agreement with those earlier sheep studies, the medial retropharyngeal lymph node would be the sample of choice, together with the obex, for post-mortem surveillance.…”
Section: Implications For Surveillance Of Goat Tsesupporting
confidence: 88%
“…The early and consistent involvement of the medial retropharyngeal lymph node and the palatine tonsil has been widely reported [1, 7, 16, 19, 26, 27], and it is believed to result from the early exposure of those tissues to infectivity following ingestion of the scrapie agent [1, 27, 29]. If that were the case, it would be difficult to explain the late and inconsistent involvement of the distal ileum Peyer’s patches observed in our study.…”
Section: Discussionmentioning
confidence: 89%
“…Of all animals present in the flocks at the time of the flock cull, close to 36% was culled, and of these culled animals approximately 66% was tested, producing 191 secondary cases of classical scrapie. We note that the number of animals actually infected at the time of culling is expected to be higher than that, as infected animals will be tested positive only when they are at a sufficiently advanced stage of incubation [17,18]. Mathematical modelling would be needed to derive infection prevalence estimates from detectable prevalence; for examples of such modelling applied to clinical case surveillance data in Great Britain, see [19,20].…”
Section: Resultsmentioning
confidence: 99%